METHODOLOGY FOR MODERNIZING THE MANAGEMENT SYSTEM OF KNOWLEDGE-INTENSIVE ENTERPRISES - Elena Nikolaevna Syshchikova (Science and Innovation Center Publishing House, 2020)
The article describes the key principles that ensure the modernization of the enterprise management system from the standpoint of worldview, cognitive and technological aspects; the logic of modernizing the management system of knowledge-intensive enterprises is proposed.